Knowledge and Attitudes of Home Care Nurses in Cyprus in the Management of Cancer Pain - Hadjisavva, Ifigeneia Christou; Papastavrou, Evridiki; Kouta, Christiana (My University, 2021)
Pain is a common symptom for cancer patients. It is a problem for themselves and their relatives. Nurses are confronted with the treatment of cancer pain in their everyday clinical practice. Efficient management requires accurate and appropriate knowledge, positive attitudes, and competent evaluation skills. The aim is to explore the knowledge and attitudes of Cypriot home care nurses in pain management of cancer patients. Regarding methodology, a quantitative descriptive design was used and the data were collected with the Greek version of the McCaffery and Ferrell Nurses’ Knowledge and Attitudes Survey Regarding Pain questionnaire along with a demographic questionnaire. The sample of the study consisted of home care nurses working in non-profit organizations in Cyprus (n = 31). For the analysis of data, the SPSSv.21. was used and the statistical significance was set to the p =.05. Results revealed of the total of 35 questions only 13 were answered correctly by the 80% of the participants. Limited knowledge was reported mainly on the duration of action, the effect and dosage of Pethidine, the risk of addiction and the use of non-medication interventions. Significant differences were found to the level of knowledge as regards the age and the experience of nurses. In the case study exercise, it was found that false assessment of pain was related to wrong decisions. Nurses’ attitudes seemed to be positive. In conclusion, the study revealed the knowledge deficits and need for continuous education of home care nurses on the assessment and management of pain for patients with cancer. Empowering nurses with better skills to deal with pain, a most distressing symptom of cancer, will result in a better quality of life for patients. However, the integration of pain management within the national cancer strategies is also very important.
Keywords: Cancer; Home nursing care; Knowledge; Nursing; Pain management